2019
DOI: 10.1002/mrd.23170
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma features of Prochilodus lineatus and Brycon orbignyanus throughout two consecutives spawning seasons

Abstract: This study aims to describe seminal plasma characteristics, detect changes during and between two consecutive spawning seasons (SS), and compare plasma features between two important South American fish species. Prochilodus lineatus and Brycon orbignyanus sperm was collected over two (SS1; SS2). Each season was divided into first and second sampling periods (P1; P2). Thus, the four experimental periods were referred to as SS1P1, SS1P2, SS2P1, and SS2P2. Seminal plasma was analyzed for osmolality, pH, and Na+, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Although seminal plasma osmolality and pH are important sperm quality indicators (Kowalski & Cejko, 2019), these parameters were not associated with the other sperm quality markers evaluated in this work. The maintenance of seminal plasma osmolality and pH between 296.33–350.40 mOsm/kg, and 8.45–8.95, respectively, during the season characterizes the values usually observed for the species (Viveiros, Di Chiacchio, et al, 2019; Viveiros et al, 2016), thus providing a good environment for spermatozoa performance. The ionic composition of P. lineatus seminal plasma fluctuated throughout the reproductive period, and this has also been reported by Viveiros, Di Chiacchio, et al (2019) in this species and in Brycon orbignyanus , whereas Kuradomi et al (2016) found no differences in Piaractus mesopotamicus .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Although seminal plasma osmolality and pH are important sperm quality indicators (Kowalski & Cejko, 2019), these parameters were not associated with the other sperm quality markers evaluated in this work. The maintenance of seminal plasma osmolality and pH between 296.33–350.40 mOsm/kg, and 8.45–8.95, respectively, during the season characterizes the values usually observed for the species (Viveiros, Di Chiacchio, et al, 2019; Viveiros et al, 2016), thus providing a good environment for spermatozoa performance. The ionic composition of P. lineatus seminal plasma fluctuated throughout the reproductive period, and this has also been reported by Viveiros, Di Chiacchio, et al (2019) in this species and in Brycon orbignyanus , whereas Kuradomi et al (2016) found no differences in Piaractus mesopotamicus .…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, seasonal changes in seminal plasma osmolality have been reported in C. carpio and D. labrax (Cejko et al, 2018; Martínez‐Páramo, Diogo, Beirão, et al, 2012), and changes in seminal plasma pH have been described during the reproductive period of C. carpio (Cejko et al, 2018). Seasonal changes in sperm concentration have been reported in S. dumerili , C. carpio , S. namaycush and D. labrax (Cejko et al, 2018; Fakriadis & Mylonas, 2021; Johnson et al, 2013; Martínez‐Páramo, Diogo, Beirão, et al, 2012), and in the neotropical fish Brycon orbignyanus (Viveiros, Di Chiacchio, et al, 2019). Importantly, variations of seminal plasma constituents throughout the reproductive period have been associated with external factors and sperm characteristics (Cejko et al, 2018; Martínez‐Páramo, Diogo, Beirão, et al, 2012; Viveiros, Di Chiacchio, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations